If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + (2x + 3) + (2x + 4) = 2x + 2x + (3x + 1) Reorder the terms: 2x + (3 + 2x) + (2x + 4) = 2x + 2x + (3x + 1) Remove parenthesis around (3 + 2x) 2x + 3 + 2x + (2x + 4) = 2x + 2x + (3x + 1) Reorder the terms: 2x + 3 + 2x + (4 + 2x) = 2x + 2x + (3x + 1) Remove parenthesis around (4 + 2x) 2x + 3 + 2x + 4 + 2x = 2x + 2x + (3x + 1) Reorder the terms: 3 + 4 + 2x + 2x + 2x = 2x + 2x + (3x + 1) Combine like terms: 3 + 4 = 7 7 + 2x + 2x + 2x = 2x + 2x + (3x + 1) Combine like terms: 2x + 2x = 4x 7 + 4x + 2x = 2x + 2x + (3x + 1) Combine like terms: 4x + 2x = 6x 7 + 6x = 2x + 2x + (3x + 1) Reorder the terms: 7 + 6x = 2x + 2x + (1 + 3x) Remove parenthesis around (1 + 3x) 7 + 6x = 2x + 2x + 1 + 3x Reorder the terms: 7 + 6x = 1 + 2x + 2x + 3x Combine like terms: 2x + 2x = 4x 7 + 6x = 1 + 4x + 3x Combine like terms: 4x + 3x = 7x 7 + 6x = 1 + 7x Solving 7 + 6x = 1 + 7x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-7x' to each side of the equation. 7 + 6x + -7x = 1 + 7x + -7x Combine like terms: 6x + -7x = -1x 7 + -1x = 1 + 7x + -7x Combine like terms: 7x + -7x = 0 7 + -1x = 1 + 0 7 + -1x = 1 Add '-7' to each side of the equation. 7 + -7 + -1x = 1 + -7 Combine like terms: 7 + -7 = 0 0 + -1x = 1 + -7 -1x = 1 + -7 Combine like terms: 1 + -7 = -6 -1x = -6 Divide each side by '-1'. x = 6 Simplifying x = 6
| 35+9104(72)= | | -28x-4=0 | | X(X+1)(X+2)(X+3)=840 | | x^2+7xy+10y^2= | | 190(56)716-= | | X*(X+1)*(X+2)*(X+3)=840 | | p^2-8p-20= | | -44x-728=-772 | | -13-(-7)-2= | | 10a+5x=3b | | 1/2(12x+6)= | | 32-(19)= | | -100=5x | | 3x-(2-7)=133 | | 12+(-11)= | | p^2-21p+20= | | 6-8x=7x-10x-29 | | 3x-2(7)=x | | 4(1+c)=3(c-4) | | .592n+60=5n-12-n | | 8(4c-1)-18=30c+8 | | w^2+19w+18= | | 6(y-2)=4y-22 | | w^2-w-30= | | (6x+3y+1)-(5x+2y-3)= | | w^2+13w-30= | | -16t^2+80t-96=0 | | y=0.2189x+15.61 | | x-50=.80(x-100) | | 5(4x-3)=21x | | 4x=49+3 | | (5a+3)+(7a+5)= |